Nutrition and Lifestyle Aspects of the Elderly - Pumputienė, Ingrida; Damulevičienė, Gytė; Lisauskaitė, Gabrielė; Petereit, Rūta; Lenkutienė, Dalia; Maksimova, Laura; Pliupelis, Marius; Barčytė, Rasa; Laurinaitis, Jonas; Rimeikaitė, Skaistė; Jonušienė, Rasa (Slauga. Mokslas ir praktika, 2024)
Theses of the Presentations at the Conference (March 15, 2024) Organized by theLithuanian Society of Dietitians and the Health Care Faculty of Vilnius College
Keywords: -